Análisis del discurso político del presidente Rafael Correa el 30 de septiembre del 2010 plasmado en un video documental. - Armas Itas, Diana Grisely (2012)
The speech plays an important role in the handling of the messages sent, is complex in terms of the different modes of organization in which they can demonstrate and diverse by the set of rules and grammar rules that guide people in building appropriate speeches for every occasion. Throughout his presidency, Rafael Correa has won over fans through a good command of language.